Biomimetic manganese-eumelanin nanocomposites for combined hyperthermia-immunotherapy against prostate cancer - Yu Liu; Wenting Shang; Heng Liu; Hui Hui; Jun Wu; Wei Zhang; Pengli Gao; Kunxiong Guo; Yanli Guo; Jie Tian (Journal of Nanobiotechnology, 2022)
Abstract Pro-tumoral and immunosuppressive M2-like tumor-associated macrophages (TAMs) contribute to tumor progression, recurrence and distal metastasis. However, current TAMs-modulating therapeutic strategies often encounter challenges including insufficient immune activation, weak antigen presentation ability and unsatisfactory antitumor immune performance. Herein, cyclic RGD peptide functionalized and manganese doped eumelanin-like nanocomposites (RMnMels) are reported for combined hyperthermia-immunotherapy against PC3 prostate cancer. The RMnMels could promote M2-to-M1 macrophage repolarization via scavenging multiple reactive oxygen species and remodeling the immunosuppressive tumor microenvironment. Following near-infrared light irradiation, RMnMels-mediated thermal ablation not only could destroy tumor cells directly, but also elicit the release of damage associated molecular patterns and tumor-associated antigens, provoking robust tumor immunogenicity and strong antitumor immune responses. The results showed that RMnMels could effectively scavenge reactive oxygen species and promote M2-to-M1 macrophage repolarization both in vitro and in vivo. Synergistically enhanced anti-tumor therapeutic efficacy was achieved following single administration of RMnMels plus single round of laser irradiation, evidenced by decreased primary tumor sizes and decreased number of distant liver metastatic nodules. The as-developed RMnMels may represent a simple and high-performance therapeutic nanoplatform for immunomodulation and enhanced antitumor immune responses. Graphical Abstract